GREEN AND SUSTAINABLE FINANCE: IDENTIFY THE ISSUE AND RESEARCH GAP BASED ON ISLAMIC PERSPECTIVE - Budiharjo, Anas; Ismail, Nor Asmat; Rahim, Hainnuraqma (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Several countries that are global leaders in the Islamic financial industry have established policies regarding implementing a sustainable financial system. The policies are mandatory for both the conventional and Islamic Financial Institutions (IFIs). From this point, various issues, challenges and questions arise about how to implement sustainable finance in IFIs, which have significantly different characteristics and objectives than conventional financial institutions that develop the idea of sustainable finance. Therefore, this research aims to identify the issues and research gap in the existing green and sustainable finance model. This has been achieved through a literature survey and the content analysis used to examine, explain and describe the explicit meaning of a document. This study raised several issues related to green and sustainable finance. It also provides several research gaps that need to be filled soon. The research finding shows that the existing green and sustainable finance models do not emphasize an Islamic perspective and are inappropriate to implement in IFIs. Therefore, this study suggests that more work must be undertaken to construct a sustainable model from Islamic sources that is more appropriate for the Islamic context and reality.